2015
DOI: 10.11113/jt.v77.5983
|View full text |Cite
|
Sign up to set email alerts
|

ANTIPROLIFERATIVE EFFECT OF Dendrophthoe pentandra EXTRACTS TOWARDS HUMAN BREAST ADENOCARCINOMA CELLS (MCF-7)

Abstract: Dendrophthoe pentandra (DP) is a semi-parasitic plant. Previous studies showed that this plant possessed diverse medicinal properties. The present study was carried out to determine antiproliferative activity of various DP crude extracts. Extracts of petroleum ether, diethyl ether, chloroform, ethyl acetate and methanol, have been evaluated through IC50 value, which defined by the concentration of drug that is required for the inhibition of 50% of cell population in vitro. The determination of percentage cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 8 publications
3
10
0
Order By: Relevance
“…Zainuddin et al [21] proposed that the traditional claimed on the medicinal plant DP might be contributing to the existence of these compounds in DP. The finding of the present research project was in line with the result from Zainuddin et al [21,28] where benzoic acid, hexadecanoic acid and linolenic acid were in common. Though the GC-MS analysis derived possibility of 39 compounds of DPEA, the purity of the sample would be concerned but the result obtained still considered as valid as bioactive compounds detected supported by previous research.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Zainuddin et al [21] proposed that the traditional claimed on the medicinal plant DP might be contributing to the existence of these compounds in DP. The finding of the present research project was in line with the result from Zainuddin et al [21,28] where benzoic acid, hexadecanoic acid and linolenic acid were in common. Though the GC-MS analysis derived possibility of 39 compounds of DPEA, the purity of the sample would be concerned but the result obtained still considered as valid as bioactive compounds detected supported by previous research.…”
Section: Discussionsupporting
confidence: 82%
“…For this screening assay, malignant cell lines MCF-7 and L929 cells showed significant anti-proliferative activity. From the previous study, Zainuddin stated that different types of extract could reveal different therapeutic effects towards MCF-7 breast cancer cells [28]. The present finding in tandem of the previous work where DPEA inhibit MCF-7 cell growth in MTT treatment.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…From the literature search, DP was found out to have antiproliferative activity on breast cancer cell line T47D cell proliferation and induce apoptosis using MTS assay [27]. Another study from Zainuddin [21,28] performed MBA assay and reported that no IC 50 detected in MDCK, L929 and Vero cell lines when tested with several concentrations of the extract. This indicates that the DP extract does not show any severe cytotoxic effect on mammalian normal cells from previous studies.…”
Section: Discussionmentioning
confidence: 99%